Serologic surveillance for West Nile virus and other flaviviruses in febrile patients, encephalitic patients, and asymptomatic blood donors in northern Mexico. - Rodríguez, M. de L.; Rodríguez, Diana R.; Blitvich, Bradley J.; López Alejandro, Miguel Ángel; Fernández Salas, Ildefonso; Farfán Ale, José Arturo; Tamez, R. C.; Longoria, C. M.; Tavitas Aguilar, María Isabel; Rivas Estilla, Ana María (Vector borne and zoonotic diseases, 2010)
A clinical and serological investigation was performed to determine the presence of West Nile virus (WNV) among febrile and encephalitic patients in northern Mexico. In addition, asymptomatic blood donors were serologically assayed for WNV to determine the seroprevalence of WNV in the general population. The study cohort consisted of 1432 individuals (588 febrile patients, 44 encephalitic patients, and 800 asymptomatic blood donors). All subjects were negative for WNV IgM. Sixty subjects were reactive for dengue virus (DENV) IgM (16 blood donors and 44 febrile patients). A subset (n = 425) of individuals was also screened by ELISA for flavivirus IgG. The prevalence of flavivirus IgG in febrile patients, encephalitic patients, and blood donors ranged from 40% to 59%. A subset (n = 147) of sera reactive for flavivirus IgG was further tested by plaque reduction neutralization test. Six individuals with no history of travel during the preceding 12 months were seropositive for WNV. Another 65 individuals were seropositive for DENV1 and 24 were seropositive for DENV2. The high prevalence of dengue antibodies in northern Mexico appears to limit the incidence of WNV infection in this region. Article Summary Line: Antibodies to WNV, DENV-1, and DENV-2 were identified in humans in northern Mexico.